Criticalities of district heating in Southern Europe: Lesson learned from a CHP-DH in Central Italy. (5th February 2017) - Comodi, G.; Lorenzetti, M.; Salvi, D.; Arteconi, A.
Highlights: Criticalities of operating a gas turbine CHP-DH in Southern Europe are highlighted. Lowering the DH water operating temperature reduces thermal losses of about 7%. Installation of a CHP, sized on the yearly thermal power baseload, increases PES. High temperature HP for CHP waste heat recovery improves economic performance. Thermal energy storage allows to reduce use of boilers to satisfy peak demand. Abstract: District heating (DH) in Southern Europe is a relevant energy sector to be improved in terms of efficiency, monitoring and metering systems, without underrating investments cost. Heat losses, poor technical conditions combined with high operational costs can seriously affect competitiveness of DH. This paper analyses the criticalities of a combined heat and power (CHP) plant coupled with a DH located in Central Italy and explores possible solutions to improve efficiency and profitability. First the CHP-DH plant is described (main features and the effects on its operation produced by the reduction of DH supply water temperature). Then, the criticalities highlighted during its lifetime are put into evidence (CHP oversizing and low profitability in the present energy market). In order to overcome the above criticalities, the introduction of an internal combustion engine, a high temperature heat pump or a thermal energy storage tank in the existing CHP-DH system is analysed. Results show that the best option is the new cogeneration gas engine, sized on the baseload thermal demand, allowing both an improvement of primary energy saving and revenues. The configuration with the heat pump, instead, affects positively the profitability but not the energetic efficiency; the opposite is obtained with the TES.